PROSPEK PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL DALAM KESENIAN TRADISIONAL DI INDONESIA - mulyadi mulyadi mulyadi (jurnal.unprimdn.ac.id, 2018)
Intellectual Property Rights (IPR) are related to human creativity, and human creativity in meeting needs or solving life problems, both in art, science and technology as well as superior products of a society. Therefore, the development of science and technology accompanied by the existence of IPRs is very important. Where this research activity cannot avoid the problem of IPR if it wants a respect for rights and new innovations, and its originality. Issues regarding Intellectual Property Rights will touch various aspects such as aspects of technology, industry, social, culture, and various other aspects. However, the most important aspect when it comes to protecting intellectual property is the legal aspect. The law is expected to be able to overcome various problems that arise related to the Intellectual Property Rights. Law must be able to provide protection for intellectual work, so as to be able to develop the creative power of society which ultimately leads to the goal of the successful protection of Intellectual Property Rights.